Presence of brain metastasis differentially impacts long-term survival after first-line therapy in melanoma depending on BRAF mutation status - Placke, Jan-Malte; Rajcsanyi, Luisa Sophie; Herbst, Rudolf; Terheyden, Patrick; Utikal, Jochen; Pföhler, Claudia; Kreuter, Alexander; Mohr, Peter; Gutzmer, Ralf; Weichenthal, Michael; Meier, Friedegund; Berking, Carola; et al. (Frontiers in Immunology, 2025)
BackgroundModern therapeutic strategies have significantly improved the prognosis of advanced melanoma patients. Predictive factors of therapy response include serum LDH; however, predictive markers for long-term survival are currently largely lacking.Patients and methodsPatients diagnosed with stage IV melanoma (AJCCv8) of cutaneous origin or unknown primary were identified from the prospective multicenter German Dermatologic Cooperative Oncology Group (DeCOG) skin cancer registry ADOREG. Baseline characteristics were compared between patient groups with short-term versus long-term survival. Statistical analysis included ROC analysis and multinomial regression analysis.ResultsOf 3066 stage IV melanoma patients entered into the ADOREG between 05/2014 and 06/2021, 395 were identified for this study, of whom 301 (76.2%) survived ≤1 year, and 94 (23.8%) survived ≥5 years after stage IV diagnosis. The median follow-up time was 6 months (range 0-129 months). Regarding the baseline characteristics, only elevated serum LDH (P <0.001) was found to be independently predicting survival ≤1 year. Type of first-line therapy, immune checkpoint inhibition (ICI) versus BRAF/MEK targeted therapy (TT), was not predictive of long-term survival ≥5 years. For survival ≤1 year, the presence of brain metastases at treatment start was an independent predictor in BRAF-mutated patients regardless if they received TT (N=113; P=0<0.001) or ICI (N=69; P=0.015), but not in BRAF-wildtype patients who received ICI (N=161; P=0.47).ConclusionsLow serum LDH independently predicts long-term survival of stage IV melanoma patients in every subgroup of treatment type and BRAF status. Brain metastasis has a negative impact on long-term survival in BRAF-mutated, but not in BRAF-wildtype patients. Investigation of molecular features of brain metastases in BRAF-mutated vs. BRAF-wildtype melanomas may lead to new insights in tumor biology and may yield new therapeutic approaches.